Successful Transfer of a Model T-DNA Plasmid to E. coli Revealed Its Dependence on Recipient RecA and the Preference of VirD2 Relaxase for Eukaryotes Rather Than Bacteria as Recipients - Ohmine, Yuta; Kiyokawa, Kazuya; Yunoki, Kazuya; Yamamoto, Shinji; Moriguchi, Kazuki; Suzuki, Katsunori (Frontiers in Microbiology, 2018)
In Agrobacterium-mediated transformation (AMT) of plants, a single-strand (ss) T-DNA covalently linked with a VirD2 protein moves through a bacterial type IV secretion channel called VirB/D4. This transport system originates from conjugal plasmid transfer systems of bacteria. The relaxase VirD2 and its equivalent protein Mob play essential roles in T-DNA transfer and mobilizable plasmid transfer, respectively. In this study, we attempted to transfer a model T-DNA plasmid, which contained no left border but had a right border sequence as an origin of transfer, and a mobilizable plasmid through the VirB/D4 apparatus to Escherichia coli, Agrobacterium and yeast to compare VirD2-driven transfer with Mob-driven one. AMT was successfully achieved by both types of transfer to the three recipient organisms. VirD2-driven AMT of the two bacteria was less efficient than Mob-driven AMT. In contrast, AMT of yeast guided by VirD2 was more efficient than that by Mob. Plasmid DNAs recovered from the VirD2-driven AMT colonies showed the original plasmid structure. These data indicate that VirD2 retains most of its important functions in recipient bacterial cells, but has largely adapted to eukaryotes rather than bacteria. The high AMT efficiency of yeast suggests that VirD2 can also efficiently bring ssDNA to recipient bacterial cells but is inferior to Mob in some process leading to the formation of double-stranded circular DNA in bacteria. This study also revealed that the recipient recA gene was significantly involved in VirD2-dependent AMT, but only partially involved in Mob-dependent AMT. The apparent difference in the recA gene requirement between the two types of AMT suggests that VirD2 is worse at re-circularization to complete complementary DNA synthesis than Mob in bacteria.